You may expand the square of binomial `3x+2` using the formula such that:

`(a+b)^2 = a^2 + 2ab + b^2`

Reasoning by analogy yields:

`(3x+2)^2 = (3x)^2 + 2*3x*2 + 2^2`

`(3x+2)^2 = 9x^2 + 12x + 4`

You may expand the cube of binomial `2x+3` using the formula such that:

`(a+b)^3 = a^3 + b^3 + 3ab(a+b)`

Reasoning by analogy yields:

`(2x+3)^3 =(2x)^3 + 3^3 + 3*2x*3*(2x+3)`

`(2x+3)^3 = 8x^3 +27 + 18x(2x+3)`

Evaluating the product `(3x+2)^2(2x+3)^3` such that:

`(3x+2)^2(2x+3)^3 = (9x^2 + 12x + 4)(8x^3 + 27 + 18x(2x+3)) `

`(3x+2)^2(2x+3)^3 = 9x^2*8x^3 + 9*27x^2 + 9x^2*18x(2x+3) + 12*8x^3 + 12x*27 + 12x*18x(2x+3) + 4*8x^3 + 4*27 + 4*18x(2x+3)`

`(3x+2)^2(2x+3)^3 = 72x^5 + 243x^2 + 162x^3(2x+3) + 96x^3 + 324x + 216x^2(2x+3) + 32x^3 +108 + 72x(2x+3)`

`(3x+2)^2(2x+3)^3 = 72x^5 + 243x^2 + 324x^4 + 582x^3 + 324x + 432x^3 + 648x^2 + 32x^3 + 108 + 144x^2 + 216x`

`(3x+2)^2(2x+3)^3 = 72x^5+ 324x^4 + 1046x^3 + 1035x^2 + 540x + 108`

**Hence, expanding the binomials yields `(3x+2)^2(2x+3)^3 = 72x^5 + 324x^4 + 1046x^3 + 1035x^2 + 540x + 108.` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now